EFEKTIVITAS FORMULASI Seed Coating UMBI BAWANG MERAH TAHAP Seedling DALAM MEMACU PERTUMBUHAN BAWANG MERAH (Allium Cepa L.) - Afni, Nur; Suharman, Suharman; Hikmahwati, Hikmahwati; Cennawati, Cennawati; Djamaluddin, Erwin (AGRONIMAL: Jurnal Ilmiah Pertanian dan Peternakan, 2026)
Shallot (Allium cepa L.) is an important horticultural commodity whose productivity is strongly influenced by seed quality and early plant growth. One approach to improving seed quality and early growth performance is the application of seed coating technology using adhesive materials and biological agents. This study aimed to evaluate the effects of seed coating treatments based on carboxymethyl cellulose (CMC) combined with lime, Trichoderma, Bacillus, and mycorrhiza on germination, growth rate, and growth performance of shallot. The experiment was arranged in a completely randomized design with several seed coating treatments and a control, each replicated three times. Observed parameters included germination percentage, growth rate, root length, number of leaves, number of tillers, fresh weight, and dry weight of plants. The results showed that seed coating treatments significantly affected germination and growth rate at 3 and 5 days after sowing, as well as fresh and dry weights of shallot plants. The CMC + lime treatment produced the highest germination, growth rate, fresh weight, and dry weight, while treatments containing biological agents tended to enhance vegetative growth. In conclusion, seed coating technology using CMC combined with lime and beneficial microorganisms has the potential to improve seed quality and early growth of shallot.